PERLINDUNGAN HUKUM PASIEN TERHADAP TINDAKAN MALPRAKTIK OLEH DOKTER DALAM PERSPEKTIF HUKUM PIDANA - Sukma; Hambali Thalib; Hasbuddin Khalid (Qawanin Jurnal Ilmu Hukum, 2020)
This study aims to determine how Legal Protection of Patients against Malpractice Actions by Doctors in a Criminal Law Perspective. forms the implementation of criminal law protection to victims of crime as regulated medical inside (Health Law and Legislation). The results obtained are regulation of legalprotection given to victims of the criminal acts committed by the medical (doctor) Malpractice is notspecifically regulated by legislation, but when viewed from a legal standpoint as a whole then, severallegislations strongly associated with this criminal act, namely the Criminal Code, Law Number 36 of 2009 concerning Health, Law Number 29 of 2004 Concerning Doctor's Practice, Law Number 44 of 2009 concerning Hospitals, Law Number 8 of 1999 concerning Consumer Protection. Criminal liability on doctors for errors and omissions in providing medical services at the hospital, where doctors responsibility in the field of criminal law can be categorized as a criminal act if they meet the formulation Malpractice criminal offense.